Three-Dimensional Intraarterial Vaso Computed Tomography Depiction of Pipeline Flex with Shield Technology Flow Diverter Stent in Ruptured Blister Aneurysm of Supraclinoid Internal Carotid Artery - Rasmiranjan Padhi; Sathish Kandasamy; BalaSenthil Kumaran (Journal of Clinical Interventional Radiology ISVIR)
Blister aneurysms are intracranial arterial lesions originating at nonbranching sites of the dorsal supraclinoid internal carotid artery and basilar artery.1 Among different treatment options, the use of flow-diverting devices is gaining popularity and has the potential for becoming the standard of care.2 Radiological evaluation of flow diverter braid expansion and vessel wall apposition during procedure has become useful in preventing life-threatening complications. Incomplete coverage of an aneurysm neck, kinking, or incomplete expansion and malapposition of a stent carries a significant risk for thromboembolic events.3 4